Role of Triple Test in Evaluating Breast Lumps - Iqbal, Sajid; Tabassum, Saima; Khan, Zahid (Lietuvos chirurgija, 2023)
Breast tissue undergoes constant physiological changes in a woman’s life because of influence of endocrine hormones during and after reproductive life. These changes may present as pain, lumpiness or both in the breast. Breast lumps are feared for cancer. Thus, it is important for women with a breast lump to receive appropriate evaluation. Clinical breast examination is first step in evaluation of breast lump. The diagnostic sensitivity of clinical breast examination is high (98%) whereas its specificity is low, averaging 48%. Ultrasound is preferred in evaluation of radiologically dense breasts and in the study of breasts with augmentation mammoplasties. Micro-calcifications on mammography are considered to be important signs of breast cancer. X-ray mammography detects microcalcifications in 30–50% of breast cancers. FNAC is a cheap, cost effective and readily available routine diagnostic with a sensitivity ranging between 89% to 98% and specificity between 98% to 100% for palpable breast lumps. When combined together triple test achieves a higher sensitivity, specificity and diagnostic accuracy than any of the investigations taken alone. We conducted a prospective study to evaluate breast masses by clinical assessment, imaging and pathological examination. Results were compared with histopathology. We concluded that triple assessment in breast lumps gives superior results than any of its modalities taken alone.